BMC Veterinary Research
BMC Veterinary Research is an open access, peer-reviewed journal that considers articles on all aspects of veterinary science and medicine, including the epidemiology, diagnosis, prevention and treatment of medical conditions of domestic, companion, farm and wild animals, as well as the biomedical processes that underlie their health. .